2010
DOI: 10.1186/1471-2458-10-259
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary impairment after tuberculosis and its contribution to TB burden

Abstract: BackgroundThe health impacts of pulmonary impairment after tuberculosis (TB) treatment have not been included in assessments of TB burden. Therefore, previous global and national TB burden estimates do not reflect the full consequences of surviving TB. We assessed the burden of TB including pulmonary impairment after tuberculosis in Tarrant County, Texas using Disability-adjusted Life Years (DALYs).MethodsTB burden was calculated for all culture-confirmed TB patients treated at Tarrant County Public Health bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 19 publications
3
98
2
3
Order By: Relevance
“…Patients with disease with a sympatric host-pathogen relationship were more likely to have no impairment. Previously, we showed that PIAT is more frequent and severe in certain risk groups and racial/ethnic populations and also demonstrated that PIAT could be life-long (Pasipanodya et al, 2010(Pasipanodya et al, , 2012bVecino et al, 2011). In these studies, self-reported non-Hispanic white was associated with PIAT, while various measures of socio-economic status were not.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Patients with disease with a sympatric host-pathogen relationship were more likely to have no impairment. Previously, we showed that PIAT is more frequent and severe in certain risk groups and racial/ethnic populations and also demonstrated that PIAT could be life-long (Pasipanodya et al, 2010(Pasipanodya et al, , 2012bVecino et al, 2011). In these studies, self-reported non-Hispanic white was associated with PIAT, while various measures of socio-economic status were not.…”
Section: Discussionmentioning
confidence: 70%
“…Non-Hispanic Whites suffer more frequent and severe PIAT relative to other racial groups. Increased risk for PIAT remained after controlling for cigarette smoking, healthcare access, treatment, and socioeconomic status, suggesting that other factors contributed to PIAT (Pasipanodya et al, 2010). However, pathogen factors including M. tuberculosis phylogenetic differences were not included in these studies.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…"Short-course chemotherapy" is actually long. Longterm mortality, morbidity, relapse, and resistance emergence are still problems even after "successful" therapy (20,77,78,93). Indeed, while it often said that the therapy has a 95% success rate under directly observed therapy (DOTS) programs, a look at high-TB-burden countries with good DOTS programs reveals cure rates for pulmonary TB of only 34 to 76%, and those are under study conditions (1,103).…”
mentioning
confidence: 99%